Critical Incidents During Leave From an Australian Security Hospital – A 12 Year Audit. Issue 1 (2nd January 2017) - Scott, Russ; Meehan, Tom
Abstract : All critical incidents between 2003 and 2015 relating to leave episodes from the High Security Inpatient Services, Brisbane, Australia were audited. The audit found that since March 2003, when the High Security Inpatient Service opened, there was a very small number of critical incidents related to over 46, 000 leave episodes. Of the 17 patients who went absent without permission over the 12-year study period, only 2 patients re-offended and 1 patient deliberately self-harmed during a leave episode. One patient assaulted his escort nurse during a leave and four patients attempted unsuccessfully to flee their escort nurses during escorted off-ground leave. No patient committed a serious violent offence and no patient committed suicide during an absence from leave. Only 4 of the 17 patients who went absent during leave between 2003 and 2015 remain as inpatients in the High Security Inpatient Service.